Cooking Class Contoh Protein Hewani terhadap Pola Asuh Ibu dalam Menyajikan Makanan Anak Stunting - Dedeng Nurkholik Sidik Permana; Nurharlinah Nurharlinah; Oop Ropei; Yayat Suryati; Mamat Lukman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the effect of animal protein cooking classes on mothers' upbringing in serving food for stunted children in the working area of the Cihaurbeuti Health Center. The method used is a quasi-experimental study with a non-equivalent control group with a pretest and posttest. The results showed that eight people aged less than 30 years were in the intervention group (38.1%). Then aged 35-40 years, there were eight people (38.1%), while from education, there were nine people with junior high school education (42.9 %), and 18 people worked as housewives (85.7%). In the control group, six people (30%) were less than 30 years old, then 6 (30%) were over 40 years old, while from education, ten people had junior high school education (50%), and 16 people worked as housewives—stairs (80%). The statistical results of the t-test showed an alpha of less than 0.05. In conclusion, cooking class, for example, an animal protein, affects a mother's upbringing in serving food for stunted children. Keywords: Cooking Class, Parenting, Animal Protein, Stunting